Prevalence of Hymenoptera venom allergy and its immunological markers current in adults in Poland - Nittner-Marszalska, Marita; Liebhart, Jerzy; Liebhart, Ewa; Dor, Anna; Dobek, Rafał; Obojski, Andrzej; Medrala, Wojciech (Medical science monitor, 2004)
The prevalence of insect venom allergy is still being assessed. The aim of our study was to estimate, on the basis of an interviewer-administered questionnaire survey, the frequency of post-sting allergic reactions and venom sensitization. The study was performed within the framework of the ECRHS. A random sampling of 3000 persons was selected from among 68,000 persons living in the area of Wrocław, Poland. Of the 2050 persons responding to a mailed screening questionnaire, 169 were randomly selected to complete a questionnaire designed only for insect allergy detection. Venom skin test and sIgE assessment were performed on 146 and 132 patients, respectively. Allergic post-sting symptoms were found in 20.7% of surveyed patients. Large local reactions (LLs) occurred in 11.8% and systemic reactions (SYSs) in 8.9% of the study population. SYS was most often manifested by urticaria (4.7%). The frequencies of SYS II, III and IV were 1.8%, 1.8%, and 0.6%, respectively. Only LLs were more frequent in subjects with other allergic diseases (p=0.03). The presence of positive skin tests and/or sIgE in serum were 42.8% of subjects with LL, 53.3% with SYS, and 17.1% of "asymptomatic" patients. No significant differences were found between these groups regarding venom skin test results and sIgE serum concentrations. Occurrence of sIgE to bee venom was frequently associated with the presence of sIgE to timothy grass. Insect venom allergy and asymptomatic venom sensitization in adults are common in Poland. Only some venom allergy cases are IgE dependent.